The role of endotoxin/lipopolysaccharide in surgically induced tumour growth in a murine model of metastatic disease - Pidgeon, G P (Nature Publishing Group, 1999)
Surgical removal of a primary tumour is often followed by rapid growth of previously dormant metastases. Endotoxin or lipopolysaccharide, a cell wall constituent of Gram-negative bacteria, is ubiquitously present in air and may be introduced during surgery. BALB/c mice received a tail vein injection of 10(5) 4T1 mouse mammary carcinoma cells. Two weeks later, animals were subjected to surgical trauma or an intraperitoneal injection of endotoxin (10 μg per animal). Five days later, animals which underwent open surgery, laparoscopy with air sufflation or received an endotoxin injection displayed increased lung metastasis compared to anaesthetic controls. These increases in metastatic tumour growth were reflected in increased tumour cell proliferation and decreased apoptosis within lung metastases. Circulating levels of the angiogenic cytokine, vascular endothelial growth factor (VEGF), were also elevated in these groups and correlated with increased plasma levels of endotoxin. Endotoxin treatment for 18 h (>10 ng ml(–1)) directly up-regulated VEGF production by the 4T1 tumour cells in vitro. Metastatic tumour growth in mice undergoing carbon dioxide laparoscopy, where air is excluded, was similar to anaesthetic controls. These data indicate that endotoxin introduced during surgery is associated with the enhanced growth of metastases following surgical trauma, by altering the critical balances governing cellular growth and angiogenesis. © 1999 Cancer Research Campaign